Short-Chain and Unsaturated Fatty Acids Increase Sequentially From the Lag Phase During Cold Growth of Bacillus cereus - Français, Marina; Bott, Romain; Dargaignaratz, Claire; Giniès, Christian; Carlin, Frédéric; Broussolle, Véronique; Nguyen-Thé, Christophe (Frontiers in Microbiology, 2021)
Fatty acids of two mesophilic and one psychrotrophic strains of the foodborne pathogen Bacillus cereus were analyzed by GC-MS during growth at cold (10 °C and 12 °C) versus optimal (30 °C) temperatures, and during the whole growth process (6 to 7 sampling times) from lag to stationary phase. In all these strains, a sequential change of fatty acids during cold growth was observed. Fatty acids were modified as soon as the end of lag, with an increase of the short chain fatty acids (less than 15 carbons), particularly i13. These short chain fatty acids then reached a maximum at the beginning of growth, and eventually decreased to their initial level, suggesting their importance as a rapid cold adaptation mechanism for B. cereus. In a second step, an increase in Δ5,10 di-saturated fatty acids and in mono-unsaturated fatty acids in 5 position, at the expense of unsaturation in 10, started during exponential phase and continued until the end of stationary phase, suggesting a role in growth consolidation and survival at cold temperatures. Among these unsaturated fatty acids, those produced by unsaturation of n16 increased in the three strains, while other unsaturated fatty acids increased in some strains only. This study highlights the importance of a kinetic analysis of fatty acids during cold adaptation.